Effect of Cd on the iron re-supply-induced formation of chlorophyll-protein complexes in cucumber - Sárvári, Éva (Acta Biologica Szegediensis, 2008)
Cd induced changes in the accumulation of chlorophyll-protein complexes were studied during the iron induced re-greening of iron deficient cucumber plants to see how the Cd-induced alterations develop during the thylakoid biogenesis, and whether the altered development of chlorophyll-protein complexes and the changed iron metabolism are connected. Treatment with 1 μM Cd resulted in strong decrease in iron content of leaves compared to the controls, but Cd could not be detected in the leaves. It was accompanied with strong retardation of chlorophyll synthesis and biogenesis of chlorophyll-protein complexes, particularly photo-system I, the amount of which even decreased at the later period of greening. During the re-greening, the actual efficiency of photosystem II and CO2 fixation capacity recovered totally and partially, respectively. It was concluded that both retardation of the biogenesis of the complexes due to iron and chlorophyll deficiency and degradation processes affecting mainly photosystem I were involved in Cd induced changes in the pattern of chlorophyll-protein complexes.